Distributed auditory sensory input within the mouse olfactory cortex. Issue 4 (29th November 2012) - Varga, Adrienn G.; Wesson, Daniel W.
Abstract The mammalian olfactory cortex is commonly considered critical for odor information processing and perception. It is becoming increasingly apparent, however, that the olfactory cortex receives input from multiple sensory channels. Previous work from our group demonstrated the presence of auditory sensory convergence within one olfactory cortical structure, the olfactory tubercle (OT). Interestingly, anatomical evidence for auditory input into the neighboring olfactory piriform cortex (PCX) posits the possibility that auditory sensory input is a distributed property of the olfactory cortex. To address this question, we performed in vivo extracellular recordings from the OT and PCX of anesthetized mice and measured modulations in unit firing in the presence of tones. In support for auditory sensory input being a distributed feature of the olfactory cortex, we found that 29% of units sampled within the PCX display tone‐evoked responses. This population compares with that found within the OT using the same stimuli (37%). While overall tone‐evoked response magnitudes were comparable between the two structures, tone signal : noise was significantly greater within the OT than in the PCX. No effect of tone frequency (1–55 kHz) was found within either structure, with most units being narrowly tuned to a single frequency. These results suggest that a major portion of odor‐evoked output from the olfactory bulb (i.e. that entering the OT and PCX) is subject to auditory sensory input in a manner that may modulate odor information processing, odor‐guided behaviors and perception.